Does the VR Experience Influence Visit Intentions? Case Study of Ijen Crater in Indonesia - Halimah, Nur Halimah; Satria, Dias; Prasetyia, Ferry (AIBPM Publisher, 2023)
Tourism plays a crucial role in the Indonesian economy. However, the Covid-19 pandemic has substantially impacted the tourism industry. One of the destinationsÂ that have been heavily affectedÂ is the Ijen Crater. Virtual tourism has emerged as a crucial tool for promoting destinations, including the Ijen Crater, and is helpful to both tourists and tourism managers. This study examines the influence of information access, flow, and telepresence, representing the virtual reality (VR) experience of the Ijen Crater, on tourists' intention to visit the site. Hedonic value mediates the relationship between the VR experience and visits intention on the Ijen Crater. The study involved 117 respondents who had experienced Ijen crater virtual reality, and the SEM-PLS method was used for analysis. The research findings indicate that flow and telepresence have a significant influence on hedonic value, and flow itself has an indirect effect on visit intention. While information access does not significantly impact hedonic values, information access and telepresence do not indirectly influence visit intention to The ijen crater. These findings contribute new insights for researchers, stakeholders, and managers of Ijen tourism.